THE EFFECT OF E-SERVICESCAPE DIMENSIONS ON CUSTOMER TRUST OF TOKOPEDIA E-STORE DURING COVID-19 PANDEMIC - Kurniawati, Desi Tri; Yaakop, Azizul Yadi (Jurnal Aplikasi Manajemen, 2021)
This research aims to reveal the effect of e-servicescape dimensions (aesthetic appeal, layout and functionality, and financial security) on customer trust of Tokopedia e-store. This research involved 200 respondents as the data were gained through an online questionnaire. Data analysis was run in SmartPLS software. From the test result, it is found that aesthetic appeal, layout and functionality, and financial security demonstrate a positive and significant effect on customer trust. Based on these findings, it is concluded that improving e-servicescape dimensions result in better customer trust of Tokopedia e-store. Further research may include more variables like the technology acceptance model (TAM) and e-WOM for enhancing the framework of this recent research to predict customer trust for the e-store.